SHORT-TERM AND LONG-TERM RESULTS OF MARGINAL PERIODONTAL TISSUES CORRECTION AT FRONTAL TEETH AREA - Терехов, Сергій (SWorldJournal, 2024)
laser system.It was proved, that in 7-14 days after the intervention, a less pronounced gingival hyperemia was found in the group of patients treated with the Ellman Surgitron-DF device, compared to patients treated with the usual surgical method and la